2002
DOI: 10.1016/s0014-5793(02)03682-7
|View full text |Cite
|
Sign up to set email alerts
|

Arginine metabolic pathways involved in the modulation of tumor‐induced angiogenesis by macrophages

Abstract: Neovascularization, an essential step for tumor progression and metastasis development, can be modulated by the presence of macrophages (Mps) in the tumor microenvironment. The ability of Mps to regulate the angiogenicity of the LMM3 tumor cell line was studied. Peritoneal Mps from LMM3 tumor-bearing mice (TMps) potentiate in vivo LMM3 angiogenicity. These results were con¢rmed by CD31 immunoblotting assays. The activity of TMps depended on nitric oxide synthase (NOS) and arginase (A) activity. By immunoblotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…Taking into account the fact that murine mammary adenocarcinomas arising spontaneously in BABL/c mice in our laboratory are poorly infiltrated by Mps, we showed that peritoneal Mps from 7-day tumor-bearing mice, when present at low concentrations, contribute to the enhancement of LMM3 angiogenesis by providing polyamine precursors to tumor cells [2]. Although the origin of tumor-infiltrating Mps has been discussed extensively, evidence supports both recruitment from the circulating pool of monocytes and the proliferation of the local Mps population, and it has recently been discussed that Mps could become angiogenic in the presence of diverse stimuli such as growth factors or low oxygen tension as well as soluble tumor antigens [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the fact that murine mammary adenocarcinomas arising spontaneously in BABL/c mice in our laboratory are poorly infiltrated by Mps, we showed that peritoneal Mps from 7-day tumor-bearing mice, when present at low concentrations, contribute to the enhancement of LMM3 angiogenesis by providing polyamine precursors to tumor cells [2]. Although the origin of tumor-infiltrating Mps has been discussed extensively, evidence supports both recruitment from the circulating pool of monocytes and the proliferation of the local Mps population, and it has recently been discussed that Mps could become angiogenic in the presence of diverse stimuli such as growth factors or low oxygen tension as well as soluble tumor antigens [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenic stimuli can proceed from tumor cells and/or immune cells such as lymphocytes and Mps. We have previously demonstrated the ability Mps from tumor-bearing mice to exacerbate the angiogenic response elicited by LMM3 tumor cells (derived from a murine mammary adenocarcinoma), confirmed by CD31 positivity at the angiogenic site [2]. There are several molecules, such as nitrogen metabolites, prostaglandins, vascular endothelial growth factor (VEGF), fibroblast growth factor and placental growth factor, that exert proangiogenic functions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Both in mouse tumor models and neoplastic patients, TAMs were shown to favour tumor progression and remodelling (Balkwill et al, 2005;Sica et al, 2006). As a matter of fact, ARG1 activity in TAMs is induced, among other factors, by COX2-PGE 2 pathway activated in tumor cells and results in the over-production of L-ornithine, which can be used by ODC to form polyamines (putrescine, spermidine and spermine), essential molecules required for cell proliferation and tumor vascularization (Chang et al, 2001;Davel et al, 2002).…”
Section: L-arg Metabolism In Pathology Tumorsmentioning
confidence: 99%
“…Many evidences indicate that the metabolism of L-Arg can play a role in normal immune function to prevent auto-immune response and excessive response to pathogens. Nevertheless, an increased activity of ARG and an aberrant production of NO by NOS2 have been described in patients with colon, breast, lung and prostate cancer (Cederbaum et al, 2004), affecting tumor vascularization through polyamine synthesis and NO release (Davel et al, 2002) and suppressing antitumor immune response through negative effects on tumor infiltrating lymphocytes. Myeloid cells can react both to Th1 and Th2 cytokines present in the microenvironment and express both enzymes, separately or in conjunctions Serafini et al, 2005).…”
Section: Tumor-associated Metabolismmentioning
confidence: 99%